Walkability and physical activity: a protocol for systematic review and meta-analysis - Giancarlo Bazarele Machado Bruno; Felipe Mendes Delpino; Antônio Azambuja Miragem; Leandro André Vieira Olsson; Elza Daniel de Mello (Revista Brasileira de Atividade Física e Saúde)
The appropriate area for walking, related to the flow of walking, on the sidewalks and crossing (walkability) influences the practice of physical activity. However, there is no evidence of meta-analyses that have evaluated this association. Therefore, this study presents a protocol to assess the association between walkability and physical activity. The systematic review protocol was conducted following the PRISMA 2020 guidelines and will includes a search in the following databases: PubMed, SPORTDiscus, LILACS, Web of Science, Scopus, Embase, and Cochrane. It will include observational studies, cross-sectional and longitudinal, that assessed the association between walkability in the neighborhood and physical activity. The process of study selection will be conducted independently by two reviewers. The process will start by reading the titles and abstracts of interest, followed by the full reading of the articles through the Rayyan platform. We will assess the methodological and individual quality across the studies utilizing the Newcastle Ottawa Scale (NOS) and the Chi-Squared test (I2). To test the influence of variables in the meta-analysis results, we will use, whenever possible, the meta-regression technique. The meta-analysis results will be presented as Odds Ratio (OR) with 95% confidence interval, through a random or fixed-effects model, according to estimate of clinical, statistical, and methodological heterogeneity. If possible, stratifications will be performed according to age group, sex, and physical activity levels. With the expected results, we hope that the knowledge will be useful to encourage the implementation of public policies for walkability in the neighborhood to increase physical activity levels.